Early Hepatic Dysfunction in a Large Animal Model of Nonhypotensive Sepsis - Stephen Sullivan; Michael Troster; Adam Linton (Canadian Journal of Gastroenterology)
Sepsis was induced in 12 sheep by cecal devascularization and perforation. Intravenous crystalloid was administered to maintain th e pulmonary capillary wedge pressure at preseptic levels. By 24 h there was a significant drop in albumin and alkaline phosphatase with increases in aspartate aminotransferase (AST), lactate dehydrogenase and bilirubin. By 48 h the alkaline phosphatase had returned to presepsis levels, the bilirubin continued to rise, the AST and lactate dehydrogenase had plateaued while the alhumin remained low. These biochemical alterations were confirmed by examining data from 25 sheer used in similar sepsis experiments. These data revealed that marked elevations in AST were associated with a higher central venous pressure and worse renal impairment, but there was no relationship with any other hemodynamic parameter, PO2, pH or serum lactate. Histologically these biochemical alterations were associated with extensive microvesicular fatty change at 24 h and centrilobular necrosis at 48 h. Electron microscopy revealed mitochondrial degeneration, hyperplasia of the smooth endoplasmic reticulum and intracellular cholestasis.